A new skipper species for Peru: Dalla granites (Mabille, 1898) (Lepidoptera: Hesperiidae) - Cerdeña, José Alfredo (2014)
The rare skipper Dalla granites (Mabille, 1898) (Lepidoptera: Hesperiidae), previously cited from Ecuador and Bolivia is reported for the first time in Peru.